Effect of NbC Addition on the Microstructure and Wear Resistance of Laser Cladding Nickel-Based Alloy Coatings - Liu, Yingpeng; Wang, Kaiming; Fu, Hanguang; Yang, Xiaojun; Lin, Jian (Journal of materials engineering and performance, 2024)
Laser cladding nickel-based alloy coating has dense microstructure and good bonding with base material, but its wear resistance is difficult to meet the requirements of harsh environment. In order to enhance the microhardness and wear resistance of nickel-based coatings, NbC (0.6 < d < 5 μm) was added directly to Ni45 powder to prepare laser cladding nickel-based composite coatings. By studying the microstructure, microhardness and wear resistance, it was found that the main phases in the coating were γ -Ni solid solution and precipitated phases such as Cr 23 C 6 , Cr 7 C 3 and NbC. The addition of NbC inhibits the formation of Cr 23 C 6 and the total carbide content within the coating is reduced, which limited the further improvement of the microhardness of the coating. Due to the refining effect of Nb, the dendrite arm spacing was reduced up to 64.7% of the 1# coating, and the grain size was reduced to 60.0% of the 1# coating, and the coatings demonstrate better wear resistance during frictional wear.